2020
DOI: 10.1155/2020/4303140
|View full text |Cite
|
Sign up to set email alerts
|

Betacyanin as Bioindicator Using Time-Temperature Integrator for Smart Packaging of Fresh Goat Milk

Abstract: Smart packaging is a packaging system with embedded sensor or indicator technology, which provides information on the quality of the product, especially perishable foods such as goat milk. One application of smart packaging is to use a time-temperature bioindicator. The purpose of this study was to determine the quality of fresh goat milk during storage at freezing temperatures (−20 ± 2°C) for 31 days and room temperature (25 ± 3°C) for 24 hours using a time-temperature indicator by utilizing a natural dye bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…However, to obtain such information, further studies are needed. Recently, betalains have been applied as the indicator in intelligent packaging films for monitoring the spoilage of fish 14 (Table 1), shrimps, 13,16 and fresh goat's milk 15 . Notably, the pink color of betacyanins in the film can be turned into a yellow color, owing to the fact that the pigments are gradually degraded into betalamic acid during the absorption of TVB‐N into the films 16 .…”
Section: Roles Of Natural Pigments In Monitoring Food Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, to obtain such information, further studies are needed. Recently, betalains have been applied as the indicator in intelligent packaging films for monitoring the spoilage of fish 14 (Table 1), shrimps, 13,16 and fresh goat's milk 15 . Notably, the pink color of betacyanins in the film can be turned into a yellow color, owing to the fact that the pigments are gradually degraded into betalamic acid during the absorption of TVB‐N into the films 16 .…”
Section: Roles Of Natural Pigments In Monitoring Food Qualitymentioning
confidence: 99%
“…In recent years, anthocyanins from various sources, such as purple cabbage, 11 purple sweet potato 2,6 and grapes, 12 have been incorporated into indicator film to act as a pH-responsive indicator. Likewise, in many studies, betalains, which derive from cactus pear 13 and the peel of dragon fruit, [14][15][16] can be used as a pH indicator for on-package indicator films.…”
Section: Introductionmentioning
confidence: 99%
“…The dye may vary in reaction to product changes during storage. The utilization of synthetic dyes such as bromothymol blue and methyl red or natural types of dyes involving yellow betaxanthin pigments and red-violet betacyanin, obtained from red dragon fruit can be exhibited ( 74 , 75 ), conducted a study to assess the fresh quality of goat milk when stored for 31 days at freezing temperatures (−20 ± 2°C) and 24 h at room temperature (25 ± 2°C), by utilization of bioindicator films placed externally on milk bottles. The results revealed that color alterations in the bioindicator film were more visible at room temperature, compared to that of freezing temperature.…”
Section: Preservation Of Goat Milk By Novel Techniquesmentioning
confidence: 99%
“…Similarly, the utilization of bio-indicators described in the present study, developed for evaluating the quality and microbiology of goat milk at different times and temperature combinations could be considered as a novel method. This approach could be adopted for authenticating the quality of goat milk on commercial scale ( 75 ). Previous studies on goat milk suggeested the heat-dependent pasteurization methods, but the latest research proved that pulsed electric field treatment could be used as an alternative to the conventional pasteurization method to obtain better results.…”
Section: What Does the Current Review Add To The Existing Knowledge?mentioning
confidence: 99%
“…Colour indicators are applied by indirect contact with food and generally sensitive to environmental changes such as temperature and pH [1]. To produce colorimetric indicator, some natural pigments have been utilized as colorimetric sensor compound, such as betacyanin [2] and anthocyanin [3].…”
Section: Introductionmentioning
confidence: 99%